Limited Retention of Wildfire‐Derived PAHs and Trace Elements in Indoor Environments. Issue 1 (3rd January 2019) - Kohl, Lukas; Meng, Meng; de Vera, Joan; Bergquist, Bridget; Cooke, Colin A.; Hustins, Sarah; Jackson, Brian; Chow, Chung‐Wai; Chan, Arthur W. H.
Abstract: Wildfires are increasing in prevalence and intensity and emit large quantities of persistent organic and inorganic pollutants. Recent fires have caused elevated concerns that residual pollutants in indoor environments pose a long‐term health hazard to residents; however, to date no studies have investigated how long fire‐derived pollutants are retained in indoor environments. We quantified polycyclic aromatic hydrocarbons and toxic trace elements in ground ashes from the 2016 wildland‐urban interface fires in Fort McMurray (Alberta, Canada) and in house dust from 64 homes. We document residual arsenic pollution from local building fires but found no evidence that forest fire ash remained in households 14 months after the fire. Overall, house dust pollutant concentrations were equal or lower than in other locations unaffected by wildfires. Given the current and future concerns over wildfire impacts, this study provides importance evidence on the degree of their long‐term effects on the residential environment. Plain Language Summary: Wildfires release large amounts of toxic pollutants like heavy metals and polycyclic aromatic hydrocarbons. So far, it remains unknown if and how long these pollutants stay in local houses after a fire. We collected house dust samples from 64 houses in Fort McMurray (Alberta, Canada), where a wildfire forced the evacuation of all 88, 000 residents and destroyed 15% of buildings. Our study found that 14 months after the fire, pollutant concentrations in Fort McMurray house dust were lower than in other Canadian cities. We furthermore show two different types of ashes that were produced during the fire. First, ashes from burned buildings contained high concentrations of arsenic, chromium, and copper likely produced from treated wood. Traces of arsenic from these ashes could still be found at the time of our study. Second, ashes from burned forests contained high concentrations of polycyclic aromatic hydrocarbon but not heavy metals. We found no evidence that pollutants from this second type of ashes remained in Fort McMurray house dust. Key Points: Fourteen months after a major wildfire, house dust concentrations of PAH and heavy metals were similar or lower than in background studies Ashes from buildings contained high concentrations of As. Traces of these ashes were detected in dust from highly affected neighborhoods Ashes from forests contained elevated concentrations of PAH but not heavy metals. We did not detect evidence of residual forest ash